GEOGRAPHIC ANALYSIS OF SOCIO-ENVIRONMENTAL SEGREGATION OF THE CITY OF SAN JOSE - Quesada-Thompson, Greyty (2014)
One of the main problems that arises due to urban growth is limiting the populations access to basic resources to meet their needs. The city of San Jose is no exception to this phenomenon, proof of this is the level of socio-environmental segregation as is presented below. Socio-environmental segregation is determined by the accessibility and availability of public spaces, public green spaces and the provision of social facilities, allowing us to analyze the approach to urban ecology and from a geographic perspective to determine the sites with higher or lower level of socio-environmental segregation. With the verification and relation of these variables, we can statistically determine the current level of segregation in the districts of San Jose, which allows us to define, territorially, “social zones” present in the city.